Fatigue failure analysis of pin-loaded lugs (Fracture and Structural Integrity, 2015)
In the present paper, mathematical models are proposed in order to analyze the strength of pinloaded lugs with semi-elliptical crack and through-the-thickness crack. The crack growth investigation of considered crack configurations tackles the fatigue life evaluation and the crack path simulation of semi-elliptical crack. The residual strength is estimated by applying the two-parameter driving force model. The numerical and analytical approaches are employed for the stress intensity factor calculation. Experimental fatigue crack growth data are used in order to verify efficiency of the developed models. A good correlation between fatigue crack growth estimations and experimental observations is obtained.
Keywords: Cyclic loading; Strength estimation; Crack path; FEM